Principals' Perspectives on Teachers' Creativity in English Language Classroom: A Blind Spot in English Language Education in Nigeria (2023)
This study investigated the views of selected school principals through in-depth interview on the extent to which English Language teachers exhibited creativity in their classroom practices. The findings of this study highlighted a pressing need for addressing the deficiency in creative teaching among teachers, which directly impacts students' engagement and learning of English Language. While it cannot be controverted that English Language teacher preparation programme in Nigeria produce dedicated and well-qualified teachers, many of these teachers lack creativity in English Language teaching. This is a blind spot in the teaching ofEnglish language that needs attention. Many past studies concentrated more on English Language teachers' lesson preparation and delivery than deployment of creativity as a way of increasing levels of learning outcomes on the part of learners and preparing them with the flexible skills they need for the future. Recommendations were made to inform policy interventions and professional development initiatives, geared towards enhancing the quality of English Language education in Nigeria.